(untitled) (International conference on multidisciplinary science, 2026)
This article provides a scientific analysis of the histophysiological characteristics of the cardiac conduction system, specifically the bundle of His and Purkinje fibers, as well as the activity of pacemaker cells that form the basis of cardiac automatism. The study examines the mechanisms of cardiac impulse generation and conduction, their physiological foundations at the cellular level, and the significance of ion channel activity. Disruptions of cardiac conduction, particularly the causes of blocks and arrhythmias, are explained at cellular and molecular levels. The article also reviews modern approaches to the detection of cardiac rhythm disorders and their clinical assessment in medical practice.